2019
DOI: 10.2147/ott.s195537
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy and safety of nivolumab for metastatic biliary tract cancer</p>

Abstract: ObjectivePD-1 inhibitors have improved efficacy in many cancers. There are currently no reports of the use of PD-1 inhibitors, such as nivolumab, for metastatic biliary tract cancer (mBTC). This study reviewed the efficacy and safety of nivolumab for mBTC with the aim of exploring ways to improve efficacy and survival.MethodsThirty patients with mBTC were voluntarily treated with nivolumab at the PLA General Hospital. Nivolumab 3 mg/kg was administered. Progression-free survival (PFS) and overall survival were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Overall, in advanced BTC, additional analyses are needed to identify predictive biomarkers. received nivolumab as second-line therapy or later) 22. Among all 30 patients, ORR was 20.0% and median PFS was 3.1 (95% CI, 2.13-4.06) months; PFS was unaffected by PD-L1 expression (P = .801) 22.…”
mentioning
confidence: 99%
“…Overall, in advanced BTC, additional analyses are needed to identify predictive biomarkers. received nivolumab as second-line therapy or later) 22. Among all 30 patients, ORR was 20.0% and median PFS was 3.1 (95% CI, 2.13-4.06) months; PFS was unaffected by PD-L1 expression (P = .801) 22.…”
mentioning
confidence: 99%
“…However, in a subgroup of patients with MSI-H PDAC (n = 22), the median OS was 4 months with a median PFS of only 2.3 months. Thus, despite their MSI-H status, these patients do not seem to have a major benefit from checkpoint inhibitors [33].…”
Section: Immunotherapy In Pancreatic Cancermentioning
confidence: 92%
“…ORR was 17.4% [34]. In another study, nivolumab treatment showed an ORR of 20% in all patients with metastatic biliary tract cancer, independently of the PD-L1 status of the tumor [35]. In dMMR biliary tract cancers, pembrolizumab achieved an ORR of 53% in a phase II study [1].…”
Section: Immunotherapy In Biliary Tract Cancermentioning
confidence: 96%
“…The PD-1 inhibitor nivolumab has also been evaluated in patients with biliary tract cancer. In a study of 30 patients with metastatic disease, nivolumab was associated with an ORR of 20% and a disease control rate of 60%; the median PFS was 3.1 months [85] . Preliminary results of an ongoing phase II trial in patients with advanced refractory biliary tract cancer indicate an ORR of 22%, with a disease control rate of 60%.…”
Section: Immune Checkpoint Inhibition For Ccamentioning
confidence: 99%